2012
DOI: 10.1128/jcm.02086-12
|View full text |Cite
|
Sign up to set email alerts
|

Similarity and Divergence of Phylogenies, Antimicrobial Susceptibilities, and Virulence Factor Profiles of Escherichia coli Isolates Causing Recurrent Urinary Tract Infections That Persist or Result from Reinfection

Abstract: In order to obtain a better molecular understanding of recurrent urinary tract infection (RUTI), we collected 75 cases with repeatedly occurring uncomplicated UTI. The genetic relationships among uropathogenic Escherichia coli (UPEC) isolates were analyzed by pulsed-field gel electrophoresis. While 39 (52%) of the RUTI cases were defined as "persistence" of the same strain as the primary infecting strain, 36 (48%) were characterized by "reinfection" with a new strain that is different from the primary strain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
53
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 40 publications
9
53
2
4
Order By: Relevance
“…In the present study, the predominant phylogenetic group was B2 (33.8%), followed by D (28.4%), A (19.6%), and B1 (18.2%). Comparing to researchers' results from China, geographically located closest to our country, Luo et al [29] and Cao et al [30] reported the most common phylogenetic group in the UPEC isolates was B2 and D. Our results support these findings. Phylogenetic group A, associated with commensal strains, represented 19.6% of isolates, which was higher than in some studies [31,32], suggesting that the gastrointestinal tract is the main reservoir of strains that may be able to colonize the urinary tract, in accordance with previous observations.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, the predominant phylogenetic group was B2 (33.8%), followed by D (28.4%), A (19.6%), and B1 (18.2%). Comparing to researchers' results from China, geographically located closest to our country, Luo et al [29] and Cao et al [30] reported the most common phylogenetic group in the UPEC isolates was B2 and D. Our results support these findings. Phylogenetic group A, associated with commensal strains, represented 19.6% of isolates, which was higher than in some studies [31,32], suggesting that the gastrointestinal tract is the main reservoir of strains that may be able to colonize the urinary tract, in accordance with previous observations.…”
Section: Discussionsupporting
confidence: 82%
“…Prevalence of chuA gene in most of the representative isolates in the study may be a pointer to the significance of iron acquisition in the pathogenesis and urovirulence of UPEC. Greater percentage (60%) of isolates in the study belonged to phylogroup D hence, corroborates the reports of Yanping et al (2012) who reported that the predominant group of UPEC recovered from UTI patients in their study belonged to phylogroup D. The finding also agrees with the report of Cao et al (2011), in a multicenter study in China, where larger percentage (54%) www.ccsenet.org/ijb International Journal of Biology Vol. 6, No.…”
Section: Discussionsupporting
confidence: 82%
“…Previously, this gene was detected in approximately 77z of UPEC isolates causing recurrent UTI in China and in 85.5z of UPEC isolates in the United States (15,24). In the study performed by Luo et al (sitA = 77z), UPEC phylogenetic group D was the most prevalent, followed by groups B2 and then A (24). However, our findings indicate that the frequency of phylogenetic group A was more than twice that of the others.…”
contrasting
confidence: 54%
“…To the best of our knowledge, there are no published data pertaining to the presence of sitA in UPEC isolates from Iran. Previously, this gene was detected in approximately 77z of UPEC isolates causing recurrent UTI in China and in 85.5z of UPEC isolates in the United States (15,24). In the study performed by Luo et al (sitA = 77z), UPEC phylogenetic group D was the most prevalent, followed by groups B2 and then A (24).…”
mentioning
confidence: 99%